Analysis of Labor Force Participation Levels and Number of Employment Through Education on Unemployment Rates in Indonesia - Adianita, Happy; Susilowati, Dados; Karisma, Devia Anindita Putri (Gorontalo Development Review, 2024)
The aim of this research is to identify the influence and explain the contribution of the labor force participation rate and the number of jobs to the unemployment rate. The location taken in this research is Indonesia, with cross-section data from 36 provinces in 2023. Data analysis in this research uses classical assumption tests and hypothesis testing with SPSS. Based on the calculation results, the level of labor force participation through education has a negative and significant influence on the unemployment rate in Indonesia. Meanwhile, the number of jobs created through education has no effect and is not significant on the unemployment rate. In addition, the labor force participation rate and number of jobs contribute to the unemployment rate of 65.9%. This confirms that the labor force participation rate and the number of jobs have a very significant influence on determining the unemployment rate. The labor force participation rate reflects how much of the population is actively looking for work, while the number of jobs indicates the availability of job opportunities in the economy.